Survival of Saccharomyces cerevisiae and Sarcina lutea at Refrigerator Temperatures - Tanguay, A. E. (1974)
Assay organisms Saccharomyces cerevisiae and Sarcina lutea, when suspended in a weak buffer and stored at refrigerator temperatures, are stable for 1 year or more.